2001
DOI: 10.1037/0278-6133.20.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Coping, control, and adjustment in type 2 diabetes.

Abstract: The relationships of both coping strategies and perceived control to psychological and physiological adjustment were investigated in 115 adults (65 women, 50 men) with Type 2 diabetes. Results showed that (a) emotional preoccupation and palliative coping were positively correlated with depression and state anxiety, whereas perceived control was negatively correlated with depression, state anxiety, and hemoglobin A tc (HbA lc ); (b) instrumental coping predicted lower depression; (c) perceived control moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
92
3
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 60 publications
10
92
3
5
Order By: Relevance
“…The engagement in health-related behaviours was related to the locus of control only in patients with excessive body weight. This result is inconsistent with the authors' assumptions and inconsistent with the results of other reports in which the conviction of influence was related both to health-related behaviours and adherence to medical recommendations in the groups of people with diabetes [3,8,9]. However, as emphasized by Morowatisharifabad et al [9], their low prediction for internal control suggests that other psychological variables undoubtedly play an important role.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The engagement in health-related behaviours was related to the locus of control only in patients with excessive body weight. This result is inconsistent with the authors' assumptions and inconsistent with the results of other reports in which the conviction of influence was related both to health-related behaviours and adherence to medical recommendations in the groups of people with diabetes [3,8,9]. However, as emphasized by Morowatisharifabad et al [9], their low prediction for internal control suggests that other psychological variables undoubtedly play an important role.…”
Section: Discussioncontrasting
confidence: 57%
“…It is recognized that the above-mentioned behaviours may directly affect health (through, e.g. reducing the level of glucose in the blood) and reduce the risk of developing serious complications [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest that an increased level of depression is associated with demographic variables such as low education, female sex, or being unmarried [9,10,11]. Furthermore, general or diabetes-specific social support was found to be associated with fewer depressive symptoms or greater emotional well-being [12,13]. It was concluded that population-based studies are needed which combine a number of risk factors for depression, as illness intrusiveness and social support can mediate the association between disease variables and depression [7].…”
mentioning
confidence: 99%
“…A long list of factors have been identified to date, female sex (3), younger age (3,17), being unmarried (3,8,18), lower socioeconomic status (10,(17)(18)(19), perceived poor physical health (3,20,21), lack of social support (22), and perceived lack of control and illness intrusiveness (23,24). Other important factors include duration of diabetes (24), having multiple complications (7,(25)(26)(27), poor glycemic control (5,8), smoking (28), and type of treatment for diabetes (nonuse of insulin) (17).…”
mentioning
confidence: 99%
“…For instance, several studies used nonrepresentative samples from few clinical sites (17)(18)(19)(20)22,25,26,28), others used minority populations (6,10) and other subpopulations (8,12), and a few others used managed care populations (4,29). In addition, some studies included only a few participants (23,27), whereas several studies did not differentiate depressive symptomatology obtained from screening questionnaires from clinical diagnoses obtained from diagnostic interview schedules (2). Most importantly, several of these earlier studies did not adequately control for confounding.…”
mentioning
confidence: 99%